Overexpression of the LexA-regulated tisAB RNA in E. coli inhibits SOS functions; implications for regulation of the SOS response - Weel-Sneve, Ragnhild (Oxford University Press, 2008)
The DNA damage induced SOS response in Escherichia coli is initiated by cleavage of the LexA repressor through activation of RecA. Here we demonstrate that overexpression of the SOS-inducible tisAB gene inhibits several SOS functions in vivo. Wild-type E. coli overexpressing tisAB showed the same UV sensitivity as a lexA mutant carrying a noncleavable version of the LexA protein unable to induce the SOS response. Immunoblotting confirmed that tisAB overexpression leads to higher levels of LexA repressor and northern experiments demonstrated delayed and reduced induction of recA mRNA. In addition, induction of prophage λ and UV-induced filamentation was inhibited by tisAB overexpression. The tisAB gene contains antisense sequences to the SOS-inducible dinD gene (16 nt) and the uxaA gene (20 nt), the latter encoding a dehydratase essential for galacturonate catabolism. Cleavage of uxaA mRNA at the antisense sequence was dependent on tisAB RNA expression. We showed that overexpression of tisAB is less able to confer UV sensitivity to the uxaA dinD double mutant as compared to wild-type, indicating that the dinD and uxaA transcripts modulate the anti-SOS response of tisAB. These data shed new light on the complexity of SOS regulation in which the uxaA gene could link sugar metabolism to the SOS response via antisense regulation of the tisAB gene.